Marking and Quantifying IL-17A-Producing Cells In Vivo - Price, April E.; Reinhardt, R. Lee; Liang, Hong-Erh; Locksley, Richard M. (PLOS ONE, 2012)
Interleukin (IL)-17A plays an important role in host defense against a variety of pathogens and may also contribute to the pathogenesis of autoimmune diseases. However, precise identification and quantification of the cells that produce this cytokine in vivo have not been performed. We generated novel IL-17A reporter mice to investigate expression of IL-17A during Klebsiella pneumoniae infection and during experimental autoimmune encephalomyelitis, conditions previously demonstrated to potently induce IL-17A production. In both settings, the majority of IL-17A was produced by non-CD4+ T cells, particularly γδ T cells, but also invariant NKT cells and other CD4−CD3ε+ cells. As measured in dual-reporter mice, IFN-γ-producing Th1 cells greatly outnumbered IL-17A-producing Th17 cells throughout both challenges. Production of IL-17A by cells from unchallenged mice or by non-T cells under any condition was not evident. Administration of IL-1β and/or IL-23 elicited rapid production of IL-17A by γδ T cells, invariant NKT cells and other CD4−CD3ε+ cells in vivo, demonstrating that these cells are poised for rapid cytokine production and likely comprise the major sources of this cytokine during acute immunologic challenges.